Extrinsic Subclavian Vein Compression after Osteosynthesis of a Midshaft Clavicular Fracture in an Athlete - Luciano A. Rossi; Nicolas S. Piuzzi; Santiago L. Bongiovanni; Ignacio Tanoira; Gaston Maignon; Maximiliano Ranalletta (Case Reports in Orthopedics)
Clavicle fractures are common injuries. Traditionally, nonsurgical management has been favored; however, recent evidence has emerged indicating that operative fixation produces lower nonunion rates, better functional outcomes, improved cosmesis, and greater patient satisfaction. Although clavicle fixation has been considered a safe procedure, several complications related to plate fixation have been reported. We report a case of a 21-year-old basketball player that had a vascular complication associated with internal fixation of a clavicle fracture. An external compression of the subclavian vein was attributed to a long screw of a precontoured clavicular plate. Although vascular complications associated with clavicle fixation are rare, they may be limb and even life threating. It is advisable that surgeons take measures to avoid them especially when placing the medial screws.